Electrochemical and Spectroelectrochemical Characterization of Graphene Electrodes Derived from Solution‐Based Exfoliation. Issue 4 (9th March 2015) - Campos Hernández, Tania; Fernández Blanco, A. Cristina; Williams, Aled T.; Velický, Matěj; Patten, Hollie V.; Colina, Alvaro; Dryfe, Robert A. W.; Rees, Neil V.
Abstract Solution phase exfoliation of graphite to yield multilayer graphene is used to form transparent electrodes, when transferred to polymer substrates. The electrochemical performance of these electrodes is determined and their use as optically‐transparent electrodes for spectro‐electrochemical applications is described.